Genetics and Gene Therapy 2017
DOI: 10.4324/9781315254517-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Secrets and the Family

Abstract: Med.L.Rev. Genetic Secrets and the Family 131 14 Skene, ibid. at 5. 15 Skene, ibid. at 6. A linkage test 'uses genetic markers with variable sequences, within or close to the mutant gene of interest, to track it within the family': National Health and Medical Research Council, Ethical Aspects of Human Genetic Testing: An Information Paper (Australian Government Publishing Service 2000) at 23, available at . 16 That is, deletions, duplications, inversions, base subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that HBOC clients disclose genetic information from a sense of familial responsibility, enacting a kind of relational autonomy (D'Agincourt-Canning 2006;Hallowell et al 2003)-the active consideration of one's obligations and responsibilities to others when making personal autonomous decisions (Bell and Bennett 2001). Davey et al (2006) note that relational elements may already inform genetic counselor practice, in so far as genetic counselors routinely encourage their clients to disclose genetic information to their families (as supported by studies above), thereby promoting the client's relational autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that HBOC clients disclose genetic information from a sense of familial responsibility, enacting a kind of relational autonomy (D'Agincourt-Canning 2006;Hallowell et al 2003)-the active consideration of one's obligations and responsibilities to others when making personal autonomous decisions (Bell and Bennett 2001). Davey et al (2006) note that relational elements may already inform genetic counselor practice, in so far as genetic counselors routinely encourage their clients to disclose genetic information to their families (as supported by studies above), thereby promoting the client's relational autonomy.…”
Section: Introductionmentioning
confidence: 99%